Determination rock quality designation RQD basis on joints - Keykha, Hamed A.; Kim Huat, Bujang (Electronic Journal of Geotechnical Engineering, 2011)
This paper is a critical review on the role of joints in determination of rock quality designation (RQD) in observation plane. It show that the analyzing joint sets with using simple method like get data from surface of rock mass, can be effective to indicate RQD. It is estimated by counting joint volumetric Jv and compared with weighted joint density (WJD).